Is Submucosal Injection Helpful in Cold Snare Polypectomy for Small Colorectal Polyps? - Ji Hyun Song; Shai Friedland (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims Cold snare polypectomy (CSP) is an effective method of polyp removal for small colorectal polyps. However, the effect of submucosal injection in cold snare endoscopic mucosal resection (CS-EMR) for small polyps is unclear. Therefore, this study aimed to evaluate the effect of submucosal injection in CS-EMR for small polyps. Methods Between 2018 and 2019, 100 consecutive small colorectal polyps (5-10 mm) were identified in 58 patients. The first 50 consecutive polyps were removed by CS-EMR, and the remaining 50 were removed by CSP. Demographic data, clinical data, endoscopic findings, procedure times, complication rates, and pathology data were collected. Results No difference in the complete resection rate was observed between the CS-EMR and CSP groups. A total of 9 polyps showed post-polypectomy bleeding (7 had immediate bleeding, 1 had delayed bleeding, and 1 had both immediate and delayed bleeding). No difference in the bleeding rate was observed between the two groups. In multivariate analysis, warfarin (odds ratio [OR], 42.334; 95% confidence interval [CI], 1.006-1,781.758) and direct-acting oral anticoagulants (OR, 35.244; 95% CI, 3.853-322.397) showed a significantly increased risk of bleeding. Conclusions The effect of submucosal injection in CSP was not significant for small colorectal polyps.